2012
DOI: 10.1161/circulationaha.111.069153
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bisphenol A Concentration and Risk of Future Coronary Artery Disease in Apparently Healthy Men and Women

Abstract: Background-The endocrine-disrupting chemical bisphenol A (BPA) is widely used in food and beverage packaging.Higher urinary BPA concentrations were cross-sectionally associated with heart disease in National Health and Nutrition Examination Survey (NHANES) and NHANES 2005-2006, independent of traditional risk factors. Methods and Results-We included 758 incident coronary artery disease (CAD) cases and 861 controls followed for 10.8 years from the European Prospective Investigation of Cancer-Norfolk UK. Respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
193
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(198 citation statements)
references
References 53 publications
3
193
2
Order By: Relevance
“…It would be of considerable interest to determine the effects of BPA on ESRRA expression and metabolic activity in a wider range of different cell types, especially in light of the associations previously reported between exposure to BPA and metabolic diseases (Melzer et al 2012a(Melzer et al , 2012b. ERRa is present in a wide variety of cell types and is highly expressed in cells with elevated metabolic demand such as heart, skeletal muscle and brown adipose tissue (Eichner & Giguère 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be of considerable interest to determine the effects of BPA on ESRRA expression and metabolic activity in a wider range of different cell types, especially in light of the associations previously reported between exposure to BPA and metabolic diseases (Melzer et al 2012a(Melzer et al , 2012b. ERRa is present in a wide variety of cell types and is highly expressed in cells with elevated metabolic demand such as heart, skeletal muscle and brown adipose tissue (Eichner & Giguère 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Positive prospective associations have been reported between BPA exposure and a range of reproductive and developmental conditions including recurrent miscarriage (SugiuraOgasawara et al 2005) and externalising behaviour scores in the offspring of exposed mothers (Braun et al 2011). Urinary BPA concentrations were associated with cardiovascular disease diagnosis in large scale crosssectional (Lang et al 2008, 2012a and longitudinal studies (Melzer et al 2012b).…”
Section: Introductionmentioning
confidence: 95%
“…Several investigators found that higher BPA concentrations were associated with cardiovascular diagnoses (Lang et al 2008;vom Saal and Myers 2008;Melzer et al 2010) and incident coronary artery disease (Melzer et al 2012). In addition, Asano et al (2010) reported that BPA in the micromolar range activates Maxi-K (KCa1.1) ion channels in human coronary smooth muscle cells in culture to a degree sufficient to hyperpolarize the membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a nested case-control study reported the association between higher BPA exposure and incident coronary artery disease with a dose-response relationship. 16 However, the knowledge on how BPA affects the cardiovascular system is still limited.The cells of the cardiovascular system have estrogen receptors (␣ and ␤). These receptors are involved in antiatherogenic actions, vasodilation and preservation of vascular integrity, cardiomyocyte survival, and regulation of excitability of smooth muscle cells.…”
mentioning
confidence: 99%